(untitled) (Research, Society and Development, 2021)
Introduction: Snake accidents represent a serious public health problem due to its high incidence and severity. In Brazil, they are caused by snakes of the Crotalus, Lachesis, Bothrops and Micrurus genera. Objectives: this study aimed to investigate the prevalence of snakebites and related variables in the Lago Tucuruí Integration Region between 2010 and 2019. Methodology: From this perspective, a descriptive epidemiological study was carried out, data were obtained through the Information System of Notifiable Diseases (SINAN), tabulated and analyzed using Microsoft Excel, BioStat 5.0 and PAST 3.04 programs. The variables used were: gender, age group, education, municipality of occurrence, month of accident, snake gender, time between bite-care, severity and final evolution. Results: In the period analyzed there were 3,534 occurrences. The victims were predominantly male (77%), 20 to 39 years old (38%), with low education (61%); the Municipality of Novo Repartimento had the highest number of cases (30%) and prevalence rate per thousand inhabitants (17.19 cases/1,000 inhabitants); there was a higher frequency of events in the period of high rainfall (63%); of the accidents caused by venomous snakes (N=2,840), the Bothrops genus was responsible for the majority (78%); with regard to care, there was a predominance within 6 hours (71%) of these 45% within 3 hours; most occurrences were classified as mild (63%), with clinical evolution to cure (81%). Final considerations: The creation of an epidemiological profile of snakebite in our region is crucial to contribute to combat and control strategies aimed at the most affected areas.